Pelatihan Empati Untuk Meningkatkan Pemaafan Pada Mahasiswi Korban Kekerasan Dalam Hubungan Pacaran - Reza, Faisal Adnan; Widyana, Rahma (Universitas Islam Negeri Raden Intan Lampung, 2019)
AbstractThis study aims to determine the effect of empathy training to improve forgiveness for female students who are victims of violence in dating relationships. Research subjects were 5 female students who were victims of violence in dating relationships. This study was only an experimental group, taken from the results of the pre-test on the empathy and forgiveness scale in the low and medium categories and interviews. The research design used was the experimental design of one group group pretest-posttest design. Data collection tools used in the form of empathy, forgiveness, observation and interviews. Analysis of the data used is the Wilcoxon Rank Test to see the difference in experimental group scores between before and after treatment. The Wilcoxon Rank Test found that there was a difference in the forgiveness score in the experimental group after giving empathy with a Z = -2.023 with a significance of 0.043 (p <0.05) with the mean pre-test (X test = 36.40) lower than the mean post-test (X ̅ = 63.40). The conclusion of this study is that there are differences in forgiveness scores between before and after being given empathy training.